How much does tax erode fund excess returns?. (11th May 2019) - Chen, Zhe; Gallagher, David R.; Harman, Graham; Warren, Geoffrey J.; Xi, Lihui
Abstract: We model the tax drag from active fund management based on reported monthly holdings of active equity funds. Tax drag erodes 65 percent of the 0.74 percent excess return in Broad Market funds, but only 21 percent of the 1.80 percent excess return in Small‐Cap funds for Australian superannuation (pension) fund investors. Tax drag varies with investment style; market state, which is most detrimental during bull markets; and fund turnover. For high‐income individual investors, tax drag is exacerbated to the extent that active management only generates meaningful after‐tax excess return for Small‐Cap funds of certain styles.